Synergism between Trichuris suis and the microbial flora of the large intestine causing dysentery in pigs. - Rutter, J M (1975)
The role of the microbial flora of the large intestine in experimental Trichuris suis infection was studied by comparing the clinical syndrome in conventionally reared (CR) pigs, specific pathogen-free pigs, and gnotobiotic pigs. Thedisease in CR pigs was characterized by a severe mucohemorrhagic enteritis; in contrast, a mild catarrhal enteritis was observed in specific pathogen-free and gnotobiotic pigs.Spirochaetes and vibrio-like organisms were observed only in CR pigs and increased during the clinical phase of the disease. The clinical syndrome was not transmitted by oral administration of intestinal or fecal material from infected CR pigs to CR pigs free of T. suis. Smaller numbers of T. suis produced diarrhea in CR pigs and significantly reduced the growth rates of infected animals; clinical signs and the reduction in growth rate was prevented by incorporating an antibacterial substance (dimetridazole) in the food. Although clinical trichuriasis closely resembles swin dysentery, the two syndromes seem to be distinct. The present results suggest that a microbial component acts synergistically with T. suis to produce the severe clinical syndrome in CR pigs, but identification of the microbial component and the mechanism by which clinical signs are produced await further studies of the bacterial flora of the large intestine of pigs.